GANDHI'S EDUCATIONAL PHILOSOPHY AS A TOOL FOR SOCIAL INCLUSION - Gowher Hassan (RADJA PUBLIKA, 2023)
This research examines Mahatma Gandhi's educational philosophy, known as Nai Talim or Basic Education, and its contemporary relevance and application. At the heart of Gandhi's philosophy lies the integration of manual labour with intellectual pursuits, aiming to break societal barriers and imbue dignity in all forms of work. The study explores how Gandhian principles promote social inclusion by intertwining intellectual growth, moral development, and community engagement. Despite its rich history and continued resonance in progressive educational movements, the practical implementation of Gandhian education faces challenges in modern contexts. Conflicts with prevailing educational goals, societal attitudes, and resource constraints present obstacles. However, the research also presents recommendations and strategies for educators, policymakers, and institutions to effectively incorporate Gandhian principles into current educational practices. Through a careful and nuanced approach, Gandhi's vision of education as a tool for social inclusion offers a transformative blueprint that emphasizes holistic development, social equity, and community collaboration.